Surveillance mammography in older breast cancer survivors: Current practice patterns and patient perceptions. Issue 7 (September 2022) - Karam, Dhauna; Vierkant, Robert A.; Ehlers, Shawna; Freedman, Rachel A.; Austin, Jessica; Khanani, Sadia; Larson, Nicole L.; Loprinzi, Charles L.; Couch, Fergus; Olson, Janet E.; Ruddy, Kathryn J.
Abstract: Introduction: Although the benefits of surveillance mammography for older breast cancer survivors have not been quantified prospectively, it is unlikely that mammography provides substantial benefit (and possible that mammography is harmful) to women with limited life expectancy and a low risk for in-breast cancer events. Materials and Methods: We identified 1268 women aged 77 and older with a history of Stage I-III breast cancer, who did not undergo bilateral mastectomy, were diagnosed with cancer at least three years prior to study entry, and who had consented to be surveyed as part of the Mayo Clinic Breast Disease Registry. We mailed them a one-time survey asking about their experiences with surveillance mammography. Women with metastatic disease were excluded. The primary endpoint was whether or not women reported at least one mammogram since breast cancer surgery. Results: Eight hundred forty-six of 1268 (67%) returned the survey, 734 of whom were eligible for analysis. The median age at the time of survey was 82, and the median time since cancer diagnosis was 12 years. Ninety-three percent reported having had at least one mammogram since their initial breast cancer surgery. Seventy-nine percent reported that they had surveillance mammography annually over the prior three years, including 76% of the 491 aged 80+ and 64% of the 189 aged 85 + . Discussion: Most older breast cancer survivors who have residual breast tissue are undergoing annual mammograms. Additional educational materials may be beneficial for patients and clinicians to better individualize plans for surveillance mammography in older breast cancer survivors.